Advanced hepatocellular carcinoma with lymph node metastases showing epithelial to mesenchymal transition effectively treated with systemic chemotherapy: Report of a case. Issue 12 (15th May 2013) - Sadamori, Hiroshi; Yagi, Takahito; Shigeyasu, Kunitoshi; Umeda, Yuzo; Sugihara, Masahiro; Yokomichi, Naosuke; Ohara, Toshiaki; Nishida, Naoshi; Nagasaka, Takeshi; Goel, Ajay; Fujiwara, Toshiyoshi
<x xml:space="preserve">Abstract</x> We present a case in which combination chemotherapy was used to successfully treat hepatocellular carcinoma (HCC) with rapid progression of lymph node (LN) metastases after liver resection. In addition, epithelial to mesenchymal transition (EMT) markers were examined immunohistochemically. A 43‐year‐old man who had been diagnosed with HCC showed an enlarged LN near the hepatic artery proper. After extended left lobectomy with lymphadenectomy in the hepatoduodenal ligament, he experienced rapid progression of metastases to the para‐aortic and mediastinal LN. Partial remission was achieved after induction and maintenance of combination chemotherapy using etoposide, carboplatin, epirubicin and 5‐fluorouracil. As a consequence of this treatment, the patient survived 10 months. Immunohistochemical studies demonstrated that HCC cells in the metastatic LN showed low expression of E‐cadherin and high expression of N‐cadherin and vimentin, indicating EMT. Combination chemotherapy may prove effective for patients with HCC accompanied by LN metastases that show features of EMT.